Manajemen Nilai Pemangku Kepentingan di Perusahaan Publik vs. Privat: Pendekatan Kualitatif - Yohan Purnawan; Melisa Nur Asima Sidabutar; Julina Purba (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study examines stakeholder value management in public and private sector organizations using a qualitative approach. The research is grounded in the growing demand for transparency and good governance in the Indonesian context, which shapes how organizations manage and create value for stakeholders. The study aims to analyze stakeholder engagement strategies in both sectors, identify differences and similarities in organizational objectives, decision-making mechanisms, funding sources, and accountability, and evaluate the effectiveness of these strategies in generating long-term value (financial, social, and environmental). Data were collected through systematic literature study and analyzed using thematic and content analysis, supported by triangulation to ensure validity. The findings indicate that private sector organizations generally focus on creating economic value through market-oriented approaches such as customer loyalty programs, investor relations, and supply-chain collaboration. In contrast, public sector organizations prioritize social value through public consultation, transparency, and cross-institution collaboration. Digital technology also serves as a key driver for improving engagement efficiency and effectiveness in both sectors, although evaluation and responsiveness to feedback tend to differ due to institutional characteristics. The study provides practical recommendations to strengthen stakeholder value management performance in the digital and globalization era.